2021
DOI: 10.1038/s41467-021-23337-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-productive angiogenesis disassembles Aß plaque-associated blood vessels

Abstract: The human Alzheimer’s disease (AD) brain accumulates angiogenic markers but paradoxically, the cerebral microvasculature is reduced around Aß plaques. Here we demonstrate that angiogenesis is started near Aß plaques in both AD mouse models and human AD samples. However, endothelial cells express the molecular signature of non-productive angiogenesis (NPA) and accumulate, around Aß plaques, a tip cell marker and IB4 reactive vascular anomalies with reduced NOTCH activity. Notably, NPA induction by endothelial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 73 publications
(176 reference statements)
2
24
0
Order By: Relevance
“…"AAV-BR1", another AAV capsid mutant isolated from our AAV2 library which displays the peptide "NRGTEWD", mediates homing to ECs of the central nervous system (brain, spinal cord and retina) [194]. AAV-BR1 has been applied in various studies to assess the role of brain or retina ECs in different physiological and pathophysiological settings [336][337][338][339][340][341][342][343] and it has successfully been used in mouse models to treat the neurological impairments of incontinentia pigmenti [194,195] and Sandhoff disease [196]. In our view, the above-mentioned examples demonstrate huge experimental and therapeutic potential of AAV display peptide libraries and phage display libraries alike and both techniques will likely yield targeting peptides for additional EC subpopulations in the future.…”
Section: Adeno-associated Viral Targeting Of Ecsmentioning
confidence: 99%
“…"AAV-BR1", another AAV capsid mutant isolated from our AAV2 library which displays the peptide "NRGTEWD", mediates homing to ECs of the central nervous system (brain, spinal cord and retina) [194]. AAV-BR1 has been applied in various studies to assess the role of brain or retina ECs in different physiological and pathophysiological settings [336][337][338][339][340][341][342][343] and it has successfully been used in mouse models to treat the neurological impairments of incontinentia pigmenti [194,195] and Sandhoff disease [196]. In our view, the above-mentioned examples demonstrate huge experimental and therapeutic potential of AAV display peptide libraries and phage display libraries alike and both techniques will likely yield targeting peptides for additional EC subpopulations in the future.…”
Section: Adeno-associated Viral Targeting Of Ecsmentioning
confidence: 99%
“…This change may be attributed to the genotype rather than the cellular state, as all microglia (both typical and dark) observed in the APP-PS1 mice interacted signi cantly less with the vasculature compared to C57BL/6J typical microglia, regardless of their distance to Aß plaques and dystrophic neurites (NDM 3.571 ± 3.571% vs CTM 33.33 ± 9.245%, p = 0.0038; NTM 3.704 ± 3.704% vs CTM 33.33 ± 9.245%, p = 0.0045; FTM 6.897 ± 4.789% vs CTM 33.33 ± 9.245%, p = 0.0133) (Figure 3 G). This drastic difference in dark microglial vascular interactions observed in the aged APP-PS1 mice compared to the controls could be associated with a previously observed reduced volume of cerebral vasculature near Aß plaques, a phenomenon suggested to be caused by nonproductive angiogenesis resulting in vascular scars near Aß plaques (103).…”
Section: Resultsmentioning
confidence: 75%
“…The relationship between blood angiostatin levels and AD is controversial. In addition, a previous study found that Aβ could promote extensive neoangiogenesis leading to increased hypervascularization [ 24 ], while the cerebral microvasculature was shown to be reduced around Aβ plaques [ 25 ]. Hence, the role of Aβ in angiogenesis and how angiogenesis may contribute to the pathogenesis of AD remain unclear.…”
Section: Discussionmentioning
confidence: 99%